Novel insights in antimicrobial and immunomodulatory mechanisms of action of PepBiotics CR-163 and CR-172. (September 2022) - van Os, Nico; Javed, Ali; Broere, Femke; van Dijk, Albert; Balhuizen, Melanie D.; van Eijk, Martin; Rooijakkers, Suzan H.M.; Bardoel, Bart W.; Heesterbeek, Dani A.C.; Haagsman, Henk P.; Veldhuizen, Edwin
Highlights: PepBiotics CR-163 and CR-172 are active against ESKAPE pathogens. Both PepBiotics permeabilize the bacterial outer membrane (OM) and inner membrane (IM). PepBiotics bind and neutralize Lipopolysaccharide. PepBiotics kill bacteria in an immunologically silent manner. ABSTRACT: Objectives: Our group recently developed a new group of antimicrobial peptides termed PepBiotics, of which peptides CR-163 and CR-172 showed optimized antibacterial activity against Pseudomonas aeruginosa and Staphylococcus aureus without inducing antimicrobial resistance. In this study, the antibacterial mechanism of action and the immunomodulatory activity of these two PepBiotics was explored. Methods: RAW264.7 cells were used to determine the ability of PepBiotics to neutralize Lipopolysaccharide (LPS)-and Lipoteichoic acid (LTA)-induced activation of macrophages. Isothermal titration calorimetry and competition assays with dansyl-labeled polymyxin B determined binding characteristics to LPS and LTA. Combined bacterial killing with subsequent macrophage activation assays was performed to determine so-called 'silent killing'. Finally, flow cytometry of peptide-treated genetically engineered Escherichia coli expressing Green Fluorescent Protein (GFP) and mCherry in the cytoplasm and periplasm, respectively, further established the antimicrobial mechanism of PepBiotics. Results: Both CR-163 and CR-172 were shown to have broad-spectrum activity against ESKAPE pathogens and E. coli using a membranolytic mechanism of action. PepBiotics could exothermically bind LPS/LTA and were able to replace polymyxin B. Finally, it was demonstrated that bacteria killed by PepBiotics were less prone to stimulate immune cells, contrary to gentamicin and heat-killed bacteria that still elicited a strong immune response. Conclusions: These studies highlight the multifunctional nature of the two peptide antibiotics as both broad-spectrum antimicrobial and immunomodulator. Their ability to kill bacteria and reduce unwanted subsequent immune activation is a major advantage and highlights their potential for future therapeutic use.